2018
DOI: 10.1016/j.jbtep.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of expressive and neutral writing on respiratory sinus arrhythmia response over time

Abstract: The present study illustrates the benefits of examining changes in RSA over time. Future work with clinical samples should include additional measures and tasks to better define these mechanisms and rule out alternative hypotheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Interestingly, we found higher HF (RSA) after writing in both groups. A previous study has also found an increase in RSA after writing, but only in the expressive writing group (Sheerin, et al, 2018). This might be because in Sheerin et al (2018), RSA data was calculated as logRSA and not HF, and in shorter segments (2.5 min.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, we found higher HF (RSA) after writing in both groups. A previous study has also found an increase in RSA after writing, but only in the expressive writing group (Sheerin, et al, 2018). This might be because in Sheerin et al (2018), RSA data was calculated as logRSA and not HF, and in shorter segments (2.5 min.…”
Section: Discussionmentioning
confidence: 83%
“…It has been commonly accepted that higher HRV is linked with better emotion regulation (see Appelhans & Luecken, 2006;Mather & Thayer, 2018). Both SDNN (Seeley et al, 2016) and RSA (Bourassa et al, 2017;Sheerin, Konig, Eonta, & Vrana, 2018), have been found to increase after completing an expressive writing task, more specifically when participants wrote coherent narratives (Bourassa et al, 2017). Furthermore, those with higher RSA at baseline, benefit the most from expressive writing (Sloan & Epstein, 2005).…”
Section: Real-time Psychophysiological and Writing Correlates Of Expressive Writingmentioning
confidence: 99%
“…Expressive writing technique can be used to express problems and individual pressure through writing. Expressive writing can produce positive effects on physical and mental health [5]. Students write about negative or stressful events or thoughts, describe as much as possible their deep emotions and feelings, especially regarding academic stress so that it can be concluded that expressive writing techniques can explore emotions, stress and release negative thoughts that affect physical and psychological so that students can release the tensions caused by academic stress [6].…”
Section: Introductionmentioning
confidence: 99%